The Right Rev . Dr . Henry Brougham Bousfield : first (Anglican) Bishop of Pretoria : the first phase in the Transvaal (1879-1886) (Historia, 2021)
"Pretoria,    thou   art  a  City:    I   am  within   Thee." It   was  with   thesewords,  we  are  told,   that  Bishop  Bousfield,   first   Bishop  of  Pretoria,   crossedthe  "Aapjis"     River  and  entered  the  centre  of  his  See  on  the  7th  January,1879.   This  was  the  man  whose  untiring    effort  was  to  establish  the  Churchof  the  Province   of  South  Africa,   in  the  Transvaal,  a  task  which  called   forthe  greatest  strength  of  will   and  who  in  later  years  was  to  be  branded  as"obstinate"   and  "autocratic"    by  some  on  account  of  these same characteris-tics,  and who  was to  become one  of  the  "characters"   of  the  early  RepublicanTransvaal.The   Bishop  tells   us  that  he  was  drawn  to  the  missionary  field    fromchildhood    and   his   entrance   to   Caius   College,   Cambridge,   was   almostthwarted   by  this   impulse. He  did   not  marry   until   foreign   work   seemedquite   unlikely,    but   still   feeling   the   missionary   urge,   stipulated   that   hisbride   must  be  willing    "to   go  to  the  earth's  ends  if   called".     He  o~ce  let  itslip   out  that  he  was  willing    to  go  abroad.    Mr.   Bullock   of  the  Society  forthe  Propagation   of  the  Gospel,  came to  hear  of  it,  and  so  it  was  that  aftersix   happy   years   as  Vicar    of   Andover,   and   a   few  more   spent  in   othe!parishes,  he  was  offered  the  newly  created  Pretoria   Diocese  in  the  middleof  1876.   "I   knew  as little   of  Pretoria   or  the  Transvaal  as  others",  he  wrotelater,  and  he  declined  the  appointment   "since  a  distant  village   ip  a  DuichRepublic   seemed no  home  for  my  wife  and  children."A  year  later,  however, the  political   status  of the  Transvaal  had  changedsubstantially,   with  the  annexation  of  the  Republic   by  Sir  Theophil~(?  Shep.stone. On  the   offer   being   renewed,  the   Bishop   then   accepted  "ittq~insurance  office  did   not  so  raise  my  premiums  as to   render  it  impossil'>le."Thus   it  was  that  after  his  consecration  at  St.  Paul's   on. the  2nd  February,1878, the  "Beggar"   Bishop  sailed  from  Southampton  on  August  8th ...a9oar~the  "Danube".
Keywords: Bishop; Missionaries; Pretoria; Bishop Bousfield; Henry Brougham; Anglican